Prevalence of C-shaped mandibular second molar canals in the population of central Serbia: a cone-beam computed tomography study - Živanović, Suzana; Papić, Miloš; Radović, Mirjana; Mišić, Aleksandra; Živić, Miloš; Popović, Milica (Vojnosanitetski pregled, 2021)
Background/Aim. C-shaped canals are a complex morphological variation of the tooth root canal system that, if present, could greatly affect the outcome of endodontic therapy. The prevalence of these canal configurations varies between the populations of different ethnic and geographical origins. Therefore, the goal of this study was to analyze the prevalence and morphology of mandibular second molar C-shaped canals in the population of Central Serbia. Methods. The study included a total of 199 mandibular second molars receiving a cone-beam computed tomography (CBCT) examination and determining the presence of C-shaped canal systems, their configuration, minimal wall thickness and its relative position on axial cross-sections at the coronal, middle, and apical level. Results. The prevalence of C-shaped mandibular second molars was 5.53%. C1 canal configuration was the most frequent at the coronal cross-section, while C2 configuration was the most frequent at middle and apical cross-sections. Minimal wall thickness decreased going apically, with the mean value of 1.01 mm at the coronal, 0.87 mm at the middle, and 0.67 mm at the apical cross-sections. Minimal wall thickness was mostly directed lingually at all cross-sectional levels. Conclusion. C-shaped canals should be expected in mandibular second molars of the population of Central Serbia. CBCT was shown to be the most valuable technique to determine C-shaped canals and facilitate understanding of the C-shaped canal morphology; its implementation could improve the success of endodontic therapy, especially if the complex root canal configuration is present.